Klisze miejsca utraconego. Stereotypy w tekstach literatury pogranicza polsko-ukraińskiego/ Cliché of the lost territory. Stereotypes in the Polish-Ukrainian borderland fiction - Mirosława Kawecka (Language, Culture, Politics)
Stereotype may function as a repeated pattern or scheme used for a picturesque description. Such a sort of stereotype as cliché, is present in poetry of those Polish-Ukrainian writers whose ethnic communities and families experienced the tragedy of WWII. In their poetry, those writers tell stories about the lost homeland and ancestry. Such stories are of universal character, due to their repeatability of the used patterns and picturesque descriptions, regardless of the poet’s nationality.